Regional distribution of public incentives for firms support in Portugal - Vicente Galindo, Purificacion (2014)
PRIME is one of the best example support system because it has been indirectly financed by European founds while fully structured as a Portuguese policy instrument for support to the modernization of the entrepreneurial tissue. Further than the goal earlier pointed out, this paper has a dual aim: firstly, to supply an exploratory survey on the patterns of asymmetric use of the financing systems provided by the E.C. and, secondly, to emphasize the north/south endemic dichotomy existing in the country – a path dependence trend that should concern Portuguese policy makers deeper then it does. Methodologically, we have observed the financing execution of 14910 projects, collected from the official information portal of PRIME in Portugal. Due to limitations related to the information sources of the portal our study deals with a reduced number of variables: project location, year, industrial activity, financial program, NUT, district, investment and incentive. Nevertheless, the application of HOMALS, Cluster and Correspondence Analyses was possible, allowing conclusions about the level of effectiveness of PRIME across, both, location and sectors levels.